Sistem Informasi Monitoring Proyek Konstruksi CV Hasanah Beton Indonesia dengan Metode Earned Value Management - Rizal Naufal Farras Arkanda; Pratomo Setiaji; Wiwit Agus Triyanto (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The construction project monitoring process at CV Hasanah Beton Indonesia often presents various obstacles, such as late reporting, inaccurate data, and low efficiency in project supervision and control. These conditions make it difficult to accurately detect cost and time deviations. Our research aims to develop a web-based construction project monitoring system by applying the Earned Value Management method at CV Hasanah Beton Indonesia. The system was developed using the Laravel framework and MySQL database, with a Waterfall development model that includes the stages of requirements analysis, design, implementation, testing, and maintenance. The system design was carried out using FOD and Use Case Diagrams to illustrate the interaction between users and the system. System testing was conducted using the Black Box method to ensure all functions run according to the test scenario. Our findings show that the system is able to display performance indicators such as the Schedule Performance Index and Cost Performance Index in real-time, thereby helping to accurately detect cost and time deviations. Overall, this system improves the efficiency of the reporting process, the accuracy of project performance evaluation, and provides support for faster, more measurable, and data-driven managerial decision-making at CV Hasanah Beton Indonesia.